2008
DOI: 10.1080/07900620801923385
|View full text |Cite
|
Sign up to set email alerts
|

Households' Perceived Responsibilities in Flood Risk Management in The Netherlands

Abstract: Flood risk management in the Netherlands is on the eve of shifting primarily from prevention towards risk management, including disaster preparedness and response and citizen participation. This study explores Dutch households' perceived responsibility for taking private protection measures. Survey results (n ¼ 658) indicate that flood risk perception is low, that 73% of the respondents regard the government as primarily responsible for protection against flood damage, but that about 50% viewed disaster prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
166
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(195 citation statements)
references
References 9 publications
27
166
2
Order By: Relevance
“…In line with findings of other studies (Demeritt et al, 2011;Löfstedt and Perri, 2008;Terpstra and Guttelin, 2008), we found items related to political culture to be relevant, and an important condition affecting the effectiveness of risk communication is trust in the distributers of the information material. Our results show that trust in particular affects risk communication by shaping the perception and evaluation of the information material.…”
Section: Effects Of Risk Communication On Flood Risk Preparednesssupporting
confidence: 81%
“…In line with findings of other studies (Demeritt et al, 2011;Löfstedt and Perri, 2008;Terpstra and Guttelin, 2008), we found items related to political culture to be relevant, and an important condition affecting the effectiveness of risk communication is trust in the distributers of the information material. Our results show that trust in particular affects risk communication by shaping the perception and evaluation of the information material.…”
Section: Effects Of Risk Communication On Flood Risk Preparednesssupporting
confidence: 81%
“…Lave and Lave [50] found that residents in three Pennsylvanian communities both saw flood management as a government responsibility and lacked adequate knowledge to take flood protective actions themselves, while a Dutch study found the majority of residents see the government as having some or all responsibility for preparing for and preventing flood damage [51]. Despite these expectations, some residents in all four case study locations expressed a desire for better education and information about flood risk.…”
Section: Residents' Roles and Expectationsmentioning
confidence: 91%
“…Both participation and community involvement in the management of risks will reveal a number of distinctive local processes (Terpstra and Gutteling 2008;Schaich 2009). These include a greater awareness of losses, impacts and disaster risks at the local level (Perwais 2011).…”
Section: Introductionmentioning
confidence: 99%